1997
DOI: 10.1161/01.atv.17.9.1637
|View full text |Cite
|
Sign up to set email alerts
|

Evidence That Apolipoprotein A-I Milano Has Reduced Capacity, Compared With Wild-Type Apolipoprotein A-I, to Recruit Membrane Cholesterol

Abstract: Human carriers of apolipoprotein (apo) A-IMilano are heterozygous for an Arg173-->Cys substitution in the apoA-I primary sequence; despite severe reductions in HDL cholesterol concentrations, affected individuals do not develop coronary heart disease, suggesting that apoA-IMilano may possess antiatherogenic properties. As the beneficial effects of wild-type apoA-I are linked to its role in HDL cholesterol transport, we examined the capacity of apoA-IMilano to recruit cell cholesterol and activate lecithin:chol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

1999
1999
2012
2012

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 39 publications
2
15
0
Order By: Relevance
“…In our study, A-I(K107C) exhibited a greater efficiency in recruiting cholesterol from THP-1 macrophages, whereas A-I M (R173C) and A-I(K195C) showed decreased efflux abilities compared with wtapoA-I. The decreased efflux capacity of A-I M (R173C) was also observed by other research groups (40,41). Conversely, A-I M /A-I M , distinct from its monomer, was a more efficient acceptor of cellular cholesterols after mixing with phospholipid (42).…”
Section: Discussionsupporting
confidence: 85%
“…In our study, A-I(K107C) exhibited a greater efficiency in recruiting cholesterol from THP-1 macrophages, whereas A-I M (R173C) and A-I(K195C) showed decreased efflux abilities compared with wtapoA-I. The decreased efflux capacity of A-I M (R173C) was also observed by other research groups (40,41). Conversely, A-I M /A-I M , distinct from its monomer, was a more efficient acceptor of cellular cholesterols after mixing with phospholipid (42).…”
Section: Discussionsupporting
confidence: 85%
“…The absence of vascular disease in the carriers of apolipoprotein A-I Milano has been attributed to the increased efficiency of the mutant in promoting reverse cholesterol transport. This conjecture is supported by in vitro data from our laboratory and by data reported by Franceschini et al 42 However, opposite results have been reported by Bielicki et al 43 using a different in vitro model system.…”
Section: Structural and Functional Heterogeneity Of Hdl Particlessupporting
confidence: 85%
“…Because the ability of the Milano variant of apoA-I to promote greater cholesterol efflux than apoA-I wt is controversial, 6,37 we performed comparative experiments to address the efflux potential of lipid-free and lipid-associated apoA-I Milano (rHDL). In addition, serum and HDL from mice expressing the apoA-I Milano and apoA-I wt were compared.…”
Section: The Effect Of Apoa-i and Apoa-i Milano On Cholesterol Effluxmentioning
confidence: 99%
“…1,3,4 Lipid efflux studies are also contradictory with some reporting apoA-I Milano promotes greater cholesterol efflux, 5 and others indicating that apoA-I Milano does not enhance cholesterol mobilization. 6 A number of mechanisms have been identified by which free cholesterol (FC) moves from cells to extracellular acceptors. These pathways include aqueous diffusion, 7 SR-BImediated efflux, 8 ABCA1-mediated efflux, 9 and ABCG1-mediated efflux.…”
mentioning
confidence: 99%